Eksplorasi Etnomatematika Pada Aksesoris Dan Perlengkapan Karapan Kerbau Sumbawa - Zul'Amal, Ikhlas; Sripatmi, Sripatmi; Novitasari, Dwi (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Ethnomathematics is a science used to study how mathematics originates from a culture. This study aims to explore ethnomathematics in Sumbawa buffalo racing accessories and equipment. This type of research is qualitative with an ethnographic approach. Data sources were obtained from observations, interviews with cultural figures, buffalo racing owners, and sandro or shamans. Data analysis used an ethnographic approach consisting of the following stages: (1) determining informants who have in-depth knowledge, (2) conducting interviews to gather information, (3) making ethnographic notes in the form of written documentation, (4) asking descriptive questions to gain a general overview, (5) analyzing the results of ethnographic interviews to find themes, (6) conducting domain analysis to identify cultural data, (7) asking structural questions to determine the relationships between elements in one domain, (8) conducting taxonomic analysis to group data, (9) writing ethnography based on the researcher's findings, and (10) validation. The results of the study show that: 1) the meanings contained in the accessories and equipment of Sumbawa buffalo racing are courage, peace, fertility, and strength. 2) the mathematical concepts or principles in the accessories and equipment of Sumbawa buffalo racing are two-dimensional geometry (rhombus, circle, trapezoid, and triangle), three-dimensional geometry (cylinder and cone), analytical geometry (hyperbola and hyperboloid) and transformation and regularity geometry (repeating patterns, parallel lines, perpendicular lines, midpoints, and right angles).